دراسة عملية على الميزة النسبية الظاهرية لصادرات سورية من زيت الزيتون وكيفية تعزيزها إلى قدرة تنافسية - صقر, محمد; علي, علاء (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث دراسة الميزة النسبية الظاهرية ( RCA ( التي تتمتع بها بعض المنتجات السورية ( زيت الزيتون ) من خلال دراسة تطور إنتاجه، وتجارته الخارجية ( استيراد وتصدير ) ضمن الفترة المدروسة وموقع هذا المنتج في التجارة الخارجية السورية، كما يركز البحث على اختبار التنافسية النسبية للمنتج المدروس وذلك باستخدام مؤشر ( RCA ) الذي يقوم بتحليل البيانات التجارية ويقدم تصوراً عن وجود ميزة نسبية للصادرات السورية من هذا المنتج ويظهر العلاقة بين حصة المنتج من الصادرات السورية بالنسبة للصادرات العالمية. تخلص الدراسة إلى أن قطاع زيت الزيتون السوري يحقق ميزة نسبية تصديرية جيدة لذا يجب ضرورة الاهتمام بهذا القطاع والاستفادة من ميزته النسبية والعمل على تعزيزها إلى قدرة تنافسية لتستطيع سورية الدخول والثبات في الأسواق العالمية ومنافسة الدول الأخرى المنتجة والمصدرة له . The Search deals with the Study of the Revealed Comparative Advantage that some Syrian products have (olive oil as an example), through studying its production, its foreign trade (import - export) during the studied period. The study, also, deals with the importance of these products in the Syrian foreign trade. The study focuses on testing the relative competition advantage of the studied product using the indicator (RCA) that analyzes the commercial data and offers clear idea about the existence of the comparative advantage in Syrian exports of this product and shows the relation between the Syrian share of exported olive oil and the share of the other countries of the world. Finally, the Search finds that Syrian olive oil has an exportation comparative advantage so it is very important to take care of olive oil production and make use of its comparative advantage and strengthen it to be able to enter firmly the world's markets and compete with other producers and exporters in the world.